Impact of Social Media on Education - Gómez-Escalonilla Torrijos, Juan Diego; Cervantes Duarte, Luisa María; Casado Rodríguez, Aroa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
A review has been carried out since the PRISMA Declaration (2020), to determine what social networks students are using and what use they are making. N=142 papers were identified to which different inclusion / exclusion criteria were applied, including n=31 of them. The analysis of results shows educational advantages and disadvantages due to inappropriate use. The conclusion is reached of the need for school training for both teachers and students, both in prevention and in the suitable use of social media, through digital and socio-emotional competence.